A study on the packaging of dried deep fried squid rings - Tecson, Margaret L.
The main objective of this study was to determine he storage and packaging requirements of dried deep fried squid rings. The Wink's weight equilibrium method was used to determine the sorption isotherm of the product at 28-30°C. The critical moisture content (CMC) was experimentally determined to be 21.52%. With the value of the moisture contents at the initial and critical points, the maximum allowable WVTR requirement for a packaging material was calculated to be 0.3681 6/m^2-day at 90% RH gradient and 28-30°C. Based on literature WVTR values of packaging materials and their costs, three materials were selected, namely: Saran-coated cello/PE, foil/PE and cello foil/PE. The half value period of shelf life testing was used to determine the suitability of each material in prolonging the shelf life of the product. Results of the shelf life tests showed that foil/PE and cello foil/PE would be able to maintain the quality of the product way beyond the targeted period of one year, while saran-coated cello/PE would give the product a shelf life of a little less than a year.